2019
DOI: 10.1248/bpb.b19-00061
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Chebulic Acid on Alveolar Epithelial to Mesenchymal Transition in Response to Urban Particulate Matter Using Co-treatment and Post-treatment Exposure

Abstract: Urban particulate matter (UPM) is atmospheric particulate samples obtained from industrialized urban areas. It is known that pulmonary fibrosis can result directly or indirectly from particulate matter. In this study, the protective effect of chebulic acid (CA) against UPM-induced epithelial-mesenchymal transition (EMT) in the pulmonary alveolar epithelial (PAE) cells were investigated. Our findings revealed that PAE cells were changed from the epithelial phenotype to mesenchymal one after exposure to UPM. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Our previous studies have demonstrated CA’s anti-oxidant ability and its effectiveness in preventing hepatic fibrosis, lung damage owing to urban particulate matter, and vascular dysfunction [ 11 , 12 , 13 ]. In further agreement with previous studies, we also observed that CA (0.5–2.0 μM) significantly ( p < 0.05) prevented the formation of ROS in INS-1 β-cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have demonstrated CA’s anti-oxidant ability and its effectiveness in preventing hepatic fibrosis, lung damage owing to urban particulate matter, and vascular dysfunction [ 11 , 12 , 13 ]. In further agreement with previous studies, we also observed that CA (0.5–2.0 μM) significantly ( p < 0.05) prevented the formation of ROS in INS-1 β-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have demonstrated the effects of chebulic acid (CA, Figure 1), a phenolic compound isolated from the fruit of Terminalia chebula Retz, which exhibits anti-oxidant, anti-fibrotic, anti-inflammatory, and anti-glycative effects [10][11][12]. Recently, we verified the effect of CA on alveolar epithelial damage arising from exposure to urban particle matter [13]. However, the preventive effect of CA with respect to pancreatic β-cell damage remains unknown.…”
Section: Introductionmentioning
confidence: 88%
“…However, normal lungs we obtained were largely derived from younger donors. It has been shown that CA inhibits urban particulate matter-induced epithelial-to-mesenchymal transition in a human alveolar epithelial cell line (Lee et al, 2019) and reduces reactive oxygen species production and collagen accumulation in a human hepatic stellate cell line (Koo et al, 2016), suggesting that CA may play a multifaceted role in antifibrotic therapies.…”
Section: Qu Et Almentioning
confidence: 99%
“…Immunofluorescence staining of LX‐2 cells as performed by Lee, Pyo, Chae, Hong, Lee 20 The cells were incubated with anti‐fibronectin primary antibody (1:500, Santa Cruz Biotechnology, Dallas, TX, USA) at 4°C overnight. After this, it was added to the anti‐mouse Alexa 488 green fluorescent secondary antibody for 2 h. After then, 500 ng/mL of 4′, 6″‐diamidino‐2‐phenylindole (DAPI) stained the nuclei.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence staining of LX-2 cells as performed by Lee, Pyo, Chae, Hong, Lee 20 The cells were incubated with anti-fibronectin pri-…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%